The influence of school factors on teacher efficacy in student engagement - Curtis, Chandler S. (Kansas State University, 2014)
Teachers’ ability to engage students is in influenced by teachers’ collective efficacy beliefs. Yet, empirical evidence on the relationship between the social persuasion variables of schools and teacher collective efficacy in student engagement is limited. This study was designed to answer the following research question: “To what extent do teachers’ perceptions of professional development opportunities (PPDO), school leadership (PSL), and school use of performance feedback (PPF) relate to teachers’ collective efficacy in student engagement (CESE)?” To explore the relationship between teacher collective efficacy in student engagement and the social persuasion variables of schools, extant data from 262 teachers in a large urban school district in the United States was supplied through the Measures of Effective Teaching (MET) project. Scaled scores of independent and dependent variables were used to examine the relationship between the independent variables (perception of professional development opportunities, school leadership, and the use of performance feedback), and the dependent variable (collective efficacy in student engagement). A multiple regression of social persuasion variables was conducted to examine the relationship between the variables and to determine which variable, if any, has the most influence on the dependent variable. The multiple regression analysis showed that a combination of the independent variables of PPDO and PSL could explain 37% of the variance in CESE. Analyses also showed that PPDO had the strongest relationship with CESE. The results reinforce information from the literature review regarding the research questions and hypotheses. The social persuasion variables of schools are correlated with collective efficacy in student engagement. Perceptions of the use performance feedback, professional development opportunities, and school leadership are all significantly correlated with collective efficacy in student engagement. Out of the three social persuasion variables analyzed, only perception of professional development opportunities and school leadership explain a significant amount of the variance in collective efficacy in student engagement.
Keywords: Student engagement; School leadership; Collective efficacy; Performance feedback; Professional development; Teacher efficacy; African Studies (0293); Education, General (0515); Teacher Education (0530)